Repercusión de los niveles de gestión turística del gobierno autónomo descentralizado del cantón Urdaneta en el desarrollo del turismo del cantón Urdaneta de la provincia de los Ríos - l Torres Alvarez, Dollys Anabe (2018)
Tourism in Ecuador is currently considered one of the most preponderant activities in the country and specifically in the region, since we have different activities such as sun and beach, cultural, ethnographic among others. Tourism not only impacts the economic sector itself, but also strongly influences the results of other sectors, since they help improve the quality of life of the inhabitants, therefore they are the ones who are obliged to take care of our natural attractions. good conservation and preservation of the environment and the sector. That is why the Government is currently implementing tourism activities within the country in order to generate employment sources for more vulnerable sectors, is also carrying out tourism projects which not only access people of good economic status but also any type of person who really interested in this activity and want to help promote tourism in our country. It should be noted that nowadays our country is working nationally and internationally to enhance and promote internal and external tourism, therefore we must raise awareness and preserve in a sustainable and sustainable way all our tourist resources, in order to continue being a recognized country worldwide, making this state one of the most visited in Latin America.